Tariqa Haq Naqsyabandi As a System of Islamic Iman Building in Pontianak, West Kalimantan - Gitosaroso, Muh; Chakim, Sulkhan; Masruri, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Tariqa (Eng.: Order; Tariqa) is known as an organization focusing only on spiritual development. That is why Tariqa adherents are often trapped in rituals sometimes distancing them from the outlined Islamic Iman. This study aims to determine the extent to which the Tariqa can become a system of Iman formation. This research was conducted in one of the largest Tariqas in Pontianak, the Tariqa Haq Naqsyabandi headquartered at Perum IV Pontianak City. Based on the results of the research using a qualitative approach with phenomenological type, it was found that: 1) The Tariqa Haq Naqsyabandi has been carrying out Iman (faith)-building since the beginning of the congregation's declaration (Bai’at) of joining this Tariqa; 2) Follow-up coaching is carried out at certain times, such as Tawajjuhan, Special Teaching, Level Ups, and Incidental Teaching. This study contributes to the understanding of how Tariqa Haq Naqsyabandi systematically builds the faith of its congregation, showing that the faith-building system is not only effective but also adaptable to different contexts.